Development and validation of the motivation to publish scale-scientific articles (EMP-AC) for Peruvian university students - Tito Betancur, Madona (2023)
Objective: To design and validate the motivation to publish scale-scientific articles (EMP-AC) for Peruvian university students. Methods: This was an instrumental study in which 653 health, business, humanities and engineering students from private and state universities in the 3 regions of Peru participated. The scale was designed in 5 stages following international standards. The internal structure was assessed through both an Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Results: The content analysis by expert judges also supported the representativeness of the items related to the construction. The internal structure of the 13-item scale was confirmed through the Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) which showed a structure of three factors: commitment, behavior, and intentional state as initially proposed. Previous analyses of goodness of fit indices were satisfactory (χ2 (167) = 276.93, p  <  0.001; CFI = 0.95; TLI = 0.93; RMSEA = 0.07 [0.06–0.08]; SRMR = 0.06). Conclusion: The EMP-AC shows initial evidence of validity and reliability; therefore, it can be applied in the study of the motivation to publish scientific articles by Peruvian university students.